EZH2 Mediates Proliferation, Migration, and Invasion Promoted by Estradiol in Human Glioblastoma Cells - Del Moral-Morales, Aylin; González-Orozco, Juan Carlos; Hernández-Vega, Ana María; Hernández-Ortega, Karina; Peña-Gutiérrez, Karla Mariana; Camacho-Arroyo, Ignacio (Frontiers in Endocrinology, 2022)
Glioblastomas (GBM) are the most frequent and aggressive brain tumors. 17β-estradiol (E2) increases proliferation, migration, and invasion of human GBM cells; however underlying mechanisms are not fully understood. Zeste 2 Enhancer Homologous enzyme (EZH2) is a methyltransferase part of the Polycomb 2 repressor complex (PCR2). In GBM, EZH2 is overexpressed, and involved in the cell cycle, migration, and invasion processes. We studied the role of EZH2 in the pro-oncogenic actions of E2 in human GBM cells. Silencing or inhibition of EZH2 blocked proliferation, migration, and invasion of GBM cells induced by E2. We identified in silico additional putative estrogen response elements (EREs) at the EZH2 promoter, but E2 did not modify EZH2 expression. In silico analysis also revealed that among human GBM samples, EZH2 expression was homogeneous; in contrast, the heterogeneous expression of estrogen receptors (ERs) allowed the classification of the samples into groups. Even in the GBM cluster with high expression of ERs and those of their target genes, the expression of PCR2 target genes did not change. Overall, our data suggest that in GBM cells, pro-oncogenic actions of E2 are mediated by EZH2, without changes in EZH2 expression and by mechanisms that appear to be unrelated to the transcriptional activity of ERs.